2001
DOI: 10.1038/sj.onc.1204927
|View full text |Cite
|
Sign up to set email alerts
|

Insulin-like growth factor I stimulates motility in human neuroblastoma cells

Abstract: Motility is an important process that contributes to cancer cell spread. Growth factors are key regulators of motility in many cell types. Insulin-like growth factor I (IGF-I) causes SH-SY5Y human neuroblastoma cells to undergo dynamic morphological changes, leading to the extension of lamellipodia. IGF-I stimulated lamellipodia extension requires signaling through both phosphatidylinositol 3-kinase (PI3-K) and MAP kinase pathways. IGF-I, over a period of hours, stimulates SH-SY5Y and SHEP neuroblastoma cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
58
0

Year Published

2003
2003
2007
2007

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(64 citation statements)
references
References 36 publications
6
58
0
Order By: Relevance
“…Growth factors, particularly IGF-I and -II, represent one such class of signaling molecules. IGF-I/II signaling through IGF-IR can modulate neuroblastoma survival, differentiation, proliferation and motility (Singleton et al, 1996;Kim et al, 1997;van Golen and Feldman, 2000;Meyer et al, 2001). The current study expands on our previous reports by examining IGF-I signaling in specific neuroblastoma cell types.…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…Growth factors, particularly IGF-I and -II, represent one such class of signaling molecules. IGF-I/II signaling through IGF-IR can modulate neuroblastoma survival, differentiation, proliferation and motility (Singleton et al, 1996;Kim et al, 1997;van Golen and Feldman, 2000;Meyer et al, 2001). The current study expands on our previous reports by examining IGF-I signaling in specific neuroblastoma cell types.…”
Section: Discussionsupporting
confidence: 64%
“…We have previously reported that IGF-I treatment of N cells induces morphological changes accompanied by actin cytoskeletal rearrangement Kim and Feldman, 1998;Kim et al, 1998a) followed by neuronal differentiation . IGF-I treatment also enhances the motility of N and S cells (Meyer et al, 2001). In this report, we extended our previous studies with a more detailed examination of differential IGF-I signaling in N-and Stype neuroblastoma cell lines.…”
Section: Introductionsupporting
confidence: 57%
See 1 more Smart Citation
“…Cell motility was measured using a gold particle phagokinetic assay, as previously described (Albrecht-Buehler, 1977;Meyer et al, 2001). Briefly, glass coverslips were pre-coated with 1.5 ml of a 5 mg ml À1 solution of fibronectin in SFM overnight at 41C and then coated with a freshly prepared gold particle solution (10.6 mM sodium carbonate, 12.7 mM gold chloride and 0.0087% formaldehyde) and incubated overnight at 41C to allow the gold particles to precipitate.…”
Section: Gold Particle Assaymentioning
confidence: 99%
“…Increasing evidence indicates that IGF-I signaling is also pivotal to cell motility and invasion (LeRoith and Roberts, 2003). For example, activation of IGF-IR and subsequent activation of PI3K and mitogen-activated protein kinase pathways induces motility of neuroblastoma cells (Meyer et al, 2001). By affecting integrin relocation and association of the E-cadherin/catenin complex with the cytoskeleton, IGF-I stimulates migration of epithelial colonic cells (Andre et al, 1999) and myeloma cells (Tai et al, 2003).…”
Section: Introductionmentioning
confidence: 99%